Etika Sosial Kemasyarakatan dalam Al-Qur’an Studi Pemaknaan QS. Al-Hujurat Perspektif Tafsir Al-Mubarok - Isna Fitri Choirun Nisa’; Merita Dian Erina; Dila Alfina Nur Haliza; Azizah Jumriani Nasrum (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the uniqueness and perspective of Al-Mubarok's interpretation in interpreting Surah Al-Hujurat regarding hablumminaannas with specific social ethics. This study uses library research (library research). The results and discussion of this study show various kinds of social ethics, namely the importance of verifying a news whose clarity is not certain in paragraph 6, the command to make peace if there is a conflict between two parties is contained in paragraph 11 and there are prohibitions that must be avoided in life. It is not allowed to criticize, insult and be hostile in verse 12. The content of the explanation in Surah Al-Hujurat can be used as a source of guidance and can be applied in everyday life, especially in social life in order to create a harmonious and prosperous society. This study recommends mufassirin and academics to examine more deeply related to Tafsir Al-Mubarok which contains its own uniqueness but is easy to understand, this is a constructive effort, especially the Indonesian Muslim community in order to understand the contents of the Qur'an.